lncRNA TUG1 modulates proliferation, apoptosis, invasion, and angiogenesis via targeting miR-29b in trophoblast cells - Qian Li; Jing Zhang; Dong-Mei Su; Li-Na Guan; Wei-Hong Mu; Mei Yu; Xu Ma; Rong-Juan Yang (Human Genomics, 2019)
Abstract Background Pre-eclampsia (PE) is regarded as the leading cause of maternal and neonatal morbidity and mortality. Nevertheless, the potential mechanism for the regulation of trophoblast behaviors and the pathogenesis of PE remain largely elusive. Recently, accumulating evidence emphasized that aberrant expression of long non-coding RNAs (lncRNAs) functions as imperative regulators in human diseases, including PE. Thus, identifying PE-related specific lncRNAs to uncover the underlying molecular mechanism is of much significance. However, the functional roles and underlying mechanisms of lncRNAs in PE progression remain unclear. Method Placenta tissues obtained from patients with PE and healthy pregnant women were performed to measure TUG1 expression by qRT-PCR analysis. Transient transfections were conducted to alter TUG1 expression. Cell Counting Kit-8 (CCK-8) and flow cytometry assays were carried out to assess cell proliferation and apoptosis, respectively. Transwell and tube formation assays were performed to measure the capacity of cell invasion and angiogenesis. Moreover, the luciferase reporter assay was subjected to verify the binding relationship between TUG1 and miR-29b. Western blot analysis was performed to detect the expression of key proteins in the PI3K/AKT and ERK pathway. Results Here, we identified a lncRNA, TUG1, which was notably decreased in placental samples of PE patients. Functional experiments of loss- or gain-of-function assays also verified that ectopic expression of TUG1 promoted cell proliferation, invasion, and angiogenesis, but negatively regulated cell apoptosis, whereas TUG1 inhibition presented the opposite effects. Furthermore, mechanistic researches revealed that TUG1 could act as a molecular sponge for miR-29b, thus regulating MCL1, VEGFA, and MMP2 to modulate PE development. Conclusions Taken together, our findings demonstrated that TUG1 exerts as a critical role in PE progression, which might furnish a novel therapeutic marker for PE treatment.